STATUS RESISTENSI Aedes aegypti TERHADAP MALATHION 0,8% dan SIPERMETRIN 0,05% DI PELABUHA PULAU BAAI KOTA BENGKULU - Sudiharto, Miko; Udiyono, Ari; Kusariana, Nissa (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2020)
Aedes aegypti mosquito breeding is of an insect principal vector dbd patients the officials found. Also reflected by the high incidence rate at the current level number of dengue fever harbor of Pulau Baai lead to a durable the use of an insecticide of firefighter in controlling a vector dengue fever outbreak added of the government and the community. The use of an insecticide by KKP class III Bengkulu the working areas of harbor of Pulau Baai longer a routine procedure stand by and be devoted 3 months either in the perimeter and a buffer is malathion and sipermetrin. Malathion has been used for 27 years in a row and sipermetrin 6 years it is likely that the of resistance from the on Aedes aegypti mosquito breeding .The purpose of this research under way to find out the status of resistance from the Aedes aegypti mosquito breeding against malathion 0,8 % and sipermetrin 0,05 % account and the usage of an insecticide in a harbor the island of baai the city of Bengkulu the perimeter and of a buffer. The research is research experiment a quasi design it is the static group. Tested methods the susceptibility of using susceptibility test drives in. The number of respondents been disclosed in the research is 124 respondents in the present study. The result analysis mortality data Aedes aegypti mosquito use independent t-test there no difference the average death Aedes aegypti mosquito in the area the perimeter and buffer harbor of Pulau Baai. The analysis of interpretation vulnerability standard uses who got that Aedes aegypti mosquito that is at the port baai island has been resistant to malathion 0,8 % and sipermetrin 0,05 % ( death < 90 % ). Interviews with respondents indicated 83,87 % respondents use insecticides, households 79 % respondents use insecticides peritroid. kind of 53,78 % respondents use insecticides, fuel 20,17 % insecticides, lotion 21,85 % spray insecticides and 4,2 % bed nets. The replacement of an insecticide with ovitrap and gravitrap in the harbor of Pulau Baai to restore vulnerability Aedes aegypti mosquito.